Carotid plaque instability and cerebral atheroembolism - future directions in stroke-prevention - Hedin, Ulf; Karlöf, Eva (Thrombosis and Haemostasis)
Ischemic stroke affects more than 15 million people annually where athero embolism from unstable atherosclerotic plaques in the carotid bifurcation contributes a significant and potentially preventable aetiology. Landmark carotid endarterectomy trials conducted decades ago proved that removing high grade symptomatic stenoses outperforms medical therapy, yet accurately identifying unstable plaques, the true embolic source, remains elusive. Consequently, procedural efficacy is modest and more personalized diagnostic methods are necessary for refined risk stratification and improved stroke prevention. Plaque instability and athero-embolism from rupture of the fibrous cap is driven by a enlargement of the lipid rich necrotic core, inflammation, neovascularisation, intraplaque haemorrhage and fibrous cap thinning. Hypoxia induced angiogenesis produces fragile neovessels that bleed, generating oxidative stress and further destabilisation. Biomolecules escaping into the circulation from such lesions could flag individuals at imminent risk but imaging modalities such as magnetic resonance, computed tomography angiography or ultrasound are necessary to identify lesions at risk. Using these methods, aligning imaging phenotypes with molecular signatures of stability or vulnerability can aid in development of refined diagnostic methods. Integrating blood based- with quantitative imaging biomarkers and systems biology modelling promises a personalised diagnostic pipeline where screen for circulating signals of instability to detect individuals at risk together with non invasive imaging to localise culprit lesions create the basis for tailored surgical or pharmacologic therapy. In this review, we discuss scientific advances in the development of such strategies that possess the potential to sharpen patient selection, reduce unnecessary procedures and advance precision in stroke prevention.